Analisis Pengaruh Kualitas Pelayanan Sistem Informasi Dokumen Online Kependudukan (Si D’nok) Terhadap Tingkat Kepuasan Pengguna Layanan Di Dinas Kependudukan Dan Pencatatan Sipil Kota Semarang - Agus Bahrudin; Nadia Dwi Irmadiani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Technological developments have been utilized by Semarang City government agencies, one of which is the Semarang City Civil Registration Service in the form of Population Online Document Information System Services (SI D'nOK). The application of this application is expected to assist the community in obtaining quality population services. The results showed that the cumulative score of the service quality of the Population Online Document Information System was in the good category with a score of 82.5%. Satisfaction of service users is included in the very satisfying category with a score of 93.2%. The results of statistical calculations obtained the correlation coefficient of service quality to community satisfaction of 0.675 which means significant. The results of observations and results of interviews with key persons obtained the following research findings: a lack of number of employees or human resources in the population administration service of the Dispendukcapil City of Semarang, there is a discrepancy between the supply and demand for printing electronic KTPs, online population administration system services often experience network connectivity, still the large number of people who do not know the procedures and requirements for making e-KTP or KK so that the service process becomes long. Efforts to improve the quality of services carried out are through ball pick-up services and functioning of the sub-district office